Alterations of Functional and Structural Networks in Schizophrenia Patients with Auditory Verbal Hallucinations - Zhu, Jiajia; Wang, Chunli; Liu, Feng; Qin, Wen; Li, Jie; Zhuo, Chuanjun (Frontiers in Human Neuroscience, 2016)
Background: There have been many attempts at explaining the underlying neuropathological mechanisms of auditory verbal hallucinations (AVH) in schizophrenia on the basis of regional brain changes, with the most consistent findings being that AVH are associated with functional and structural impairments in auditory and speech-related regions. However, the human brain is a complex network and the global topological alterations specific to AVH in schizophrenia remain unclear. Methods: 35 schizophrenia patients with AVH, 41 patients without AVH and 50 healthy controls underwent resting-state functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI). The whole-brain functional and structural networks were constructed and analyzed using graph theoretical approaches. Inter-group differences in global network metrics (including small-world properties and network efficiency) were investigated. Results: We found that three groups had a typical small-world topology in both functional and structural networks. More importantly, schizophrenia patients with and without AVH exhibited common disruptions of functional networks, characterized by decreased clustering coefficient, global efficiency and local efficiency, and increased characteristic path length; structural networks of only schizophrenia patients with AVH showed increased characteristic path length compared with those of healthy controls. Conclusions: Our findings suggest that less “small-worldization” and lower network efficiency of functional networks may be an independent trait characteristic of schizophrenia, and regularization of structural networks may be the underlying pathological process engaged in schizophrenic AVH symptom expression.